Home education in the French-speaking part of Switzerland: Portrait of families, parental motivations and educational practices - Brabant, Christine; Donzé, Tristan; Favre Perret, Murielle; Bubenzer, Philipp (Swiss Journal of Educational Research, 2021)
Home education is a little-known but developing educational option. This first survey in the French-speaking part of Switzerland documents the reasons for this choice, the educational practices and the socio-demographic profile of 137 families. The reasons expressed by these parents are many and varied. Their main decision-making factors are social or pedagogical: a critique of motivation and socialization in the context of school, the search for enrichment of family relationships, an educational project pursued under parental responsibility, and a critique of cantonal educational programs and of school teaching methods. The results also reveal situations of childhood suffering in schools.